Pengaruh Job Description dan Penempatan Kerja Terhadap Kinerja Karyawan di DISDUKCAPIL Jakarta Pusat - Simon Peter Cerullo; Joseph M.J. Renwarin (UNIVERSITAS KALBIS, 2022)
The purpose of this research, to know the influence of job description and job placement on employee performance at Suku Dinas Kependudukan and Pecatatan Sipil Jakarta Pusat. The study discusses the dimensions of the research variables that are then examined to determine the effect between variables and objects. This research uses quantitative methods through survey surveys distributed through Google form to 53 respondents that were then processed using SPSS version 23 with sampling method is non probability sampling. Hypothesis test result (test T) that job description significant effect on employee performance of Buy with T count of 2.274 ≥ t table 2.00856. Job placement significant effect on employee performance with T count of 4.040 ≥ t table 2.00856 with Coefficient of determination of 65.6%.